Migration and Regional Convergence in the European Union - Gabriele Tondl; Peter Huber (European Regional Science Association (ERSA), 2011)
Migration and Regional Convergence in the European Union European migration trends in the last decade have been marked by a number of spectacular changes. In the course of the recent enlargement immigration to some EU15 countries from the CEECs has become remarkable. Nevertheless, the vast majority of the EU27 countries are net immigration countries. In face of the important immigration and the cohesion problem, the question arises whether migration had any effect on unemployment and GDP per capita levels in the 2000s. In this paper we use data from the Eurostat Regio Database and estimate whether EU regions reveal a process of convergence in unemployment and income and whether migration plays a role in this process. We further examine whether migration has a different impact on emigration and immigration regions or in converging and diverging regions. While we cannot find a significant impact of migration on unemployment, migration clearly affects per capita income growth.
Keywords: 330